Sahelian pastoralism from the perspective of variants associated with lactase persistence - Priehodová, Edita; Austerlitz, Frédéric; Čížková, Martina; Nováčková, Jana; Ricaut, François-Xavier; Hofmanová, Zuzana; Schlebusch, Carina M; Černý, Viktor (American journal of physical anthropology, 2020)
OBJECTIVES: Archeological evidence shows that first nomadic pastoralists came to the African Sahel from northeastern Sahara, where milking is reported by ~7.5 ka. A second wave of pastoralists arrived with the expansion of Arabic tribes in 7th-14th century CE. All Sahelian pastoralists depend on milk production but genetic diversity underlying their lactase persistence (LP) is poorly understood. MATERIALS AND METHODS: We investigated SNP variants associated with LP in 1,241 individuals from 29 mostly pastoralist populations in the Sahel. Then, we analyzed six SNPs in the neighboring fragment (419 kb) in the Fulani and Tuareg with the -13910*T mutation, reconstructed haplotypes, and calculated expansion age and growth rate of this variant. RESULTS: Our results reveal a geographic localization of two different LP variants in the Sahel: -13910*T west of Lake Chad (Fulani and Tuareg pastoralists) and -13915*G east of there (mostly Arabic-speaking pastoralists). We show that -13910*T has a more diversified haplotype background among the Fulani than among the Tuareg and that the age estimate for expansion of this variant among the Fulani (~8.5 ka) corresponds to introduction of cattle to the area. CONCLUSIONS: This is the first study showing that the "Eurasian" LP allele -13910*T is widespread both in northern Europe and in the Sahel; however, it is limited to pastoralists in the Sahel. Since the Fulani haplotype with -13910*T is shared with contemporary Eurasians, its origin could be in a region encompassing the Near East and northeastern Africa in a population ancestral to both Saharan pastoralists and European farmers.
Keywords: běloši; mléko; African Sahel; Ethnicity; subsistence; dieta; jednonukleotidový polymorfismus; pastoralism; Haplotypes; lactase persistence; Transients and Migrants; laktasa; osoby s přechodným pobytem a migranti; Arabs; antropologie fyzická; zvířata; Arabové; Humans; Black People; etnicita; Anthropology, Physical; haplotypy; černoši; Milk; White People; Lactase; Diet; Africa, Northern; severní Afrika; lidé; Polymorphism, Single Nucleotide; Animals